2019
DOI: 10.1021/acs.energyfuels.9b02454
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Isobutanol to Olefins and Aromatics over HZSM-5-Based Catalysts: Tuning of Product Selectivity

Abstract: Isobutanol derived from biomass can serve as a potential renewable candidate for the production of light olefins and aromatics, which are the building blocks to manufacture fuels and chemicals in the petrochemical industry. Dependent upon the product requirements, the product selectivity toward olefins or aromatics can be tuned by adjusting the reaction conditions and the properties of HZSM-5 catalysts. On bare HZSM-5, mild conditions (low temperature, low space time, and low acidity) favored the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…5а, 5b). Du et al [93] have shown that, when performing the isobutanol conversion on the 2% Ga 2 O 3 /SiO 2 catalyst for a long time, the cis/trans-2-butene ratio increases; this trend is attributed to a decrease in the yield of trans-butene due to catalyst deactivation.…”
Section: Promising Catalytic Processes For Isobutanol Transformationmentioning
confidence: 99%
See 4 more Smart Citations
“…5а, 5b). Du et al [93] have shown that, when performing the isobutanol conversion on the 2% Ga 2 O 3 /SiO 2 catalyst for a long time, the cis/trans-2-butene ratio increases; this trend is attributed to a decrease in the yield of trans-butene due to catalyst deactivation.…”
Section: Promising Catalytic Processes For Isobutanol Transformationmentioning
confidence: 99%
“…2а-2c). Du et al [93] attribute high content of ethylene and propylene in products of isobutanol transformations on HZSM-5 to the cracking of oligomers formed by oligomerization of isobutene as a primary product of isobutanol dehydration.…”
Section: Oh +H +mentioning
confidence: 99%
See 3 more Smart Citations